Problematika Persiapan Dan Pelaksanaan Ujian Disertasi: Survey Pada Mahasiswa Program Doktor Univeristas Pendidikan Indonesia - Kokom Komalasari; Tati Narawati (Universitas Pendidikan Indonesia, 2022)
The research objective is to describe and analyze students' understanding of the Standard Operating Procedure (SOP) for the Dissertation Examination. The research used a survey method, data collection techniques using a questionnaire with the help of the Google form application, and quantitative data analysis using descriptive statistics. The research subjects were 51 Doctoral Program students at the UPI graduate school who graduated in the 2020/2021 academic year. The results show that most doctoral students understand the SOP for the implementation of the dissertation exam, and doctoral students have problems with dissertation writing with similarity below 20%. Doctoral students have difficulty obtaining a predetermined foreign language score, students have issues related to the duration of the dissertation review time. provided by the commission team. Doctoral students have difficulty in making reputable journal articles and finding international journals that are appropriate to the field being studied, besides that there are also difficulties with the article submission process, experiencing difficulties in the revision process until the article is published. In terms of student readiness for the Stage 1 Exam Implementation and the Promotional Examination, doctoral students did not experience any problems or obstacles.